Organic Acid to Nitrile: A Chemoenzymatic Three-Step Route - Winkler, Margit; Horvat, Melissa; Schiefer, Astrid; Weilch, Victoria; Rudroff, Florian; Pátek, Miroslav; Martínková, Ludmila (Advanced synthesis & catalysis, 2023)
Various widely applied compounds contain cyano-groups, and this functional group serves as a chemical handle for a whole range of different reactions. We report a cyanide free chemoenzymatic cascade for nitrile synthesis. The reaction pathway starts with a reduction of carboxylic acid to aldehyde by carboxylate reductase enzymes (CARs) applied as living cell biocatalysts. The second - chemical - step includes in situ oxime formation with hydroxylamine. The final direct step from oxime to nitrile is catalyzed by aldoxime dehydratases (Oxds). With compatible combinations of a CAR and an Oxd, applied in one-pot two-step reactions, several aliphatic and aryl-aliphatic target nitriles were obtained in more than 80% conversion. Phenylacetonitrile, for example, was prepared in 78% isolated yield. This chemoenzymatic route does not require cyanide salts, toxic metals, or undesired oxidants in contrast to entirely chemical procedures.
Keywords: aldoxime dehydratase (Oxd); nitriles; carboxylic acid reductase (CAR); oxidoreductases; chemoenzymatic synthesis; cyanide-free nitrile synthesis